Effect of Transverse Acoustic Flow on the Input Impedance of Rapidly Flaring Horns - NEDERVEEN, Cornelis J. (Kees) (Archives of Acoustics, 2011)
In slowly flaring horns the wave fronts can be considered approximately planeand the input impedance can be calculated with the transmission line method (shortcones in series). In a rapidly flaring horn the kinetic energy of transverse flow addsto the local inertance, resulting in an effective increase in length when it is locatedin a pressure node. For low frequencies corrections are available. These fail at higherfrequencies when cross-dimensions become comparable to the wavelength, causingresonances in the cross-direction. To investigate this, the pipe radiating in outerspace is modelled with a finite difference method. The outer boundaries must be fullyabsorbing as the walls of an anechoic chamber. To achieve this, Berenger’s perfectlymatched layer technique is applied. Results are presented for conical horns, theyare compared with earlier published investigations on flanges. The input impedancechanges when the largest cross-dimension (outer diameter of flange or diameterof the horn end) becomes comparable to half a wavelength. This effect shifts theposition of higher modes in the pipe, influencing the conditions for mode locking,important for ease of playing, dynamic range and sound quality.